PROFILE OF STUDENTS’ MATHEMATICAL CONNECTION IN SOLVING ETHNOMATHEMATICS PROBLEMS IN TERMS OF HIGH MATHEMATICAL ABILITY : PROFIL KONEKSI MATEMATIKA MAHASISWA DALAM MENYELESAIKAN MASALAH ETNOMATEMATIKA DITINJAU DARI KEMAMPUAN MATEMATIKA TINGGI - Siti Lailiyah; Aning Wida Yanti (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
Mathematical connections are one of the five standards in mathematics learning and must have by students in the 21st century. Mathematics learning using culture (ethnomathematics) has a positive impact on students' mathematical understanding. Therefore, this research focuses on students' mathematical connections in solving ethnomathematics problems in terms of high mathematical abilities. This research aims to describe students' mathematical connections in solving ethnomathematics problems in terms of high mathematical abilities. This type of research is descriptive qualitative research. The subjects of this research were four mathematics education students at UIN Sunan Ampel Surabaya who had the highest Grade Point Average (GPA) of more than 3,5. Data was collected through written tests and interviews. The written test was used to reveal students' mathematical connection skills in solving Arek culture ethnomathematics problems. The interview used data triangulation by comparing students' answers when completing the test with what is revealed and deepening the results of the written test if there is something that needs to be confirmed. Next, the data is grouped and analyzed according to mathematical connection indicators. Based on the results of this analysis, it was found that the mathematical connections of students who had high mathematical abilities in solving ethnomathematics problems were in the less and very less categories. Meanwhile, the types of mathematical connections in the four subjects in solving ethnomathematics problems are procedural connections, comprehension connections, and equivalent representation connections.